ANALISIS KELINCAHAN DAN KECEPATAN TERHADAP KEMAMPUAN DRIBBLING ATLET SEPAKBOLA KOTA LINTAS MUARA BUNGO - IKHSAN MAULANA PUTRA; Deka Ismi Mori Saputra (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
Dribbling in football is the ability of an individual or team that has movement and skill activities and is supported by excellent physical conditions for the performer in displaying the game. Meanwhile,agility can be concluded as a person's ability to change movements agile and agile with a balance that is well maintained. Then, speed ​​(speed) is an ability that is based on a certain unit of time, the farther the distance traveled, the higher the speed. The purpose of this study was to find out the results of agility on dribbling abilities, the results of speed on dribbling abilities and the results of agility and speed together on dribbling abilities. The results of this study indicate that agility contributes to the athletic dribbling ability of 43.30%, the speed of contribution (contribution) to the athlete's dribbling ability is 24.21%, there is a contribution of agility and speed together to dribbling abilities at SSB Kota Lintas Muara Bungo football athlete. Based on data analysis, it turns out that the speed of contributing (donating) to athletes' dribbling ability is 43.59%. This means that the better the agility and speed, so in line with that the better the dribbling ability of the Cross City of Muara Bungo SSB Soccer athletes